Kenneth M. Brinkhous - Read, Marjory; Nichols, Timothy; White, Gilbert C.; Wagner, Robert H.; Roberts, Harold R. (Thrombosis and Haemostasis, 2001)
Kenneth M. Brinkhous, a beloved member of the faculty of the University of North Carolina, died at the age of 92 on December 11, 2000.